Kontextualisering Teoretiska tillämpningar i konstvetenskap: 2 - Hayden, Hans (Basic Readings in Culture and Aesthetics, 2019)
"This book is about a concept which is constantly used in many different ways, but also one of the most common concepts in humanities: context. However, the significance and use of this concept shifts between disciplines, and sometimes within the same discipline. All chapters in this edited volume address a concrete situation where this concept is used. The authors demonstrate how it can be applied in interpretations of images, buildings and places from different historical periods, and how it affects the ability to create meaning and knowledge. The interpretative action thus entails different forms of contextualisation. The book is primarily addressed to students of art history and others who take an interest in questions of visuality and visual practices. Offering not only a theoretical understanding of the concept, it strives to point out ways and possibilities of the practical use of contextualisation. This book constitutes the second volume of Theoretical Applications in Art History, which forms part of the series Basic Readings in Culture and Aesthetics."